Cellulosimicrobium Bacteremia in a Patient With Small Cell Lung Cancer: : Emergence of a New Gram-Positive Branching Rod - Soewarna, Victoria (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.